Pyrrolylquinoxaline-2-One Derivative as a Potent Therapeutic Factor for Brain Trauma Rehabilitation - Elizaveta A. Dutysheva; Marina A. Mikeladze; Maria A. Trestsova; Nikolay D. Aksenov; Irina A. Utepova; Elena R. Mikhaylova; Roman V. Suezov; Valery N. Charushin; Oleg N. Chupakhin; Irina V. Guzhova; Boris A. Margulis; Vladimir F. Lazarev (MDPI AG, 2020)
Traumatic brain injury (TBI) often causes massive brain cell death accompanied by the accumulation of toxic factors in interstitial and cerebrospinal fluids. The persistence of the damaged brain area is not transient and may occur within days and weeks. Chaperone Hsp70 is known for its cytoprotective and antiapoptotic activity, and thus, a therapeutic approach based on chemically induced Hsp70 expression may become a promising approach to lower post-traumatic complications. To simulate the processes of secondary damage, we used an animal model of TBI and a cell model based on the cultivation of target cells in the presence of cerebrospinal fluid (CSF) from injured rats. Here we present a novel low molecular weight substance, PQ-29, which induces the synthesis of Hsp70 and empowers the resistance of rat C6 glioma cells to the cytotoxic effect of rat cerebrospinal fluid taken from rats subjected to TBI. In an animal model of TBI, PQ-29 elevated the Hsp70 level in brain cells and significantly slowed the process of the apoptosis in acceptor cells in response to cerebrospinal fluid action. The compound was also shown to rescue the motor function of traumatized rats, thus proving its potential application in rehabilitation therapy after TBI.